2001
DOI: 10.1016/s0022-2275(20)31668-0
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism in primary biliary cirrhosis during simvastatin and UDCA administration

Abstract: Little is known about the effects of cholesterollowering agents in hypercholesterolemic patients with primary biliary cirrhosis (PBC). The aim of this study was to compare the changes induced by simvastatin and ursodeoxycholic acid (UDCA) on cholesterol metabolism in patients with PBC and preserved liver function. Six patients with PBC were administered simvastatin (40 mg/day) for 30 days and, after a washout period of 30 days, ursodeoxycholic acid (600 mg/day) for 30 days. Serum levels of lathosterol, campest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These differences seem to highlight opposite alterations in the lipid metabolism. PBC, indeed, is characterized by a marked increment of the enterohepatic circulation of various compounds, especially of lipid moieties, and several studies have demonstrated that cholesterol metabolism is markedly impaired for both synthesis and biliary elimination in PBC patients. , Conversely, not only are untreated celiac disease patients associated with lower concentrations of total cholesterol and high-density lipoprotein-cholesterol, but also, it seems that a reduction in serum HDL-C level is present even in the absence of gastrointestinal symptoms. , Therefore, HDL-C could be a key biomarker for the early diagnosis of CD and for the follow-up of the patients after gluten-free-diet treatment. Nonetheless, the underlying mechanisms remain still poorly understood: intestinal malabsorption, reduction of the cholesterogenesis, reduction in cholesterol-transporting lipoproteins, decreased apolipoprotein (Apo)-AI secretion from the altered small bowel mucosa, increased biliary secretion, and high fecal elimination of cholesterol have all been proposed as explanations of this phenomenon. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences seem to highlight opposite alterations in the lipid metabolism. PBC, indeed, is characterized by a marked increment of the enterohepatic circulation of various compounds, especially of lipid moieties, and several studies have demonstrated that cholesterol metabolism is markedly impaired for both synthesis and biliary elimination in PBC patients. , Conversely, not only are untreated celiac disease patients associated with lower concentrations of total cholesterol and high-density lipoprotein-cholesterol, but also, it seems that a reduction in serum HDL-C level is present even in the absence of gastrointestinal symptoms. , Therefore, HDL-C could be a key biomarker for the early diagnosis of CD and for the follow-up of the patients after gluten-free-diet treatment. Nonetheless, the underlying mechanisms remain still poorly understood: intestinal malabsorption, reduction of the cholesterogenesis, reduction in cholesterol-transporting lipoproteins, decreased apolipoprotein (Apo)-AI secretion from the altered small bowel mucosa, increased biliary secretion, and high fecal elimination of cholesterol have all been proposed as explanations of this phenomenon. , …”
Section: Discussionmentioning
confidence: 99%
“…PBC, indeed, is characterized by a marked increment of the enterohepatic circulation of various compounds, especially of lipid moieties, and several studies have demonstrated that cholesterol metabolism is markedly impaired for both synthesis and biliary elimination in PBC patients. 1,39 Conversely, not only are untreated celiac disease patients associated with lower concentrations of total cholesterol and high-density lipoprotein-cholesterol, but also, it seems that a reduction in serum HDL-C level is present even in the absence of gastrointestinal symptoms. 40,41 Therefore, HDL-C could be a key biomarker for the early diagnosis of CD and for the follow-up of the patients after gluten-free-diet treatment.…”
Section: ■ Discussionmentioning
confidence: 99%
“…141 Unsurprisingly, simvastatin use additionally decreased total cholesterol by at least 19% (p ¼ 0.01) and LDL by 26% (p ¼ 0.001). 141,142 In one RTC, while 12-month use of moderate-intensity simvastatin did significantly lower cholesterol and LDL (p ¼ 0.01), it did not significantly improve liver enzyme index or endothelial function, as measure by lipid hydroperoxides, cell adhesion molecule levels, antioxidant levels, inflammatory markers, and vascular compliance, compared with placebo even though positive trends were observed. 143…”
Section: Statin and Primary Biliary Cholangitismentioning
confidence: 96%